SIGNIFICANCE OF IRON DEFICIENCY IN RECURRENT APHTHOUS STOMATITIS - Rabbia Shabbir; Aqsa Malik; Raheela Yasmin; Atteaya Zaman; Yasir Iqbal; Ambreen Gul; Amena Rahim (Pakistan Oral & Dental Journal, 2021)
The objective of study was to measure iron levels in patients of recurrent aphthous stomatitis and compare them with control.It was a case control study conducted in biochemistry department of Islamic International Medical College Rawalpindi from 15th March 2016 to 14 March 2017.The study included 140 subjects divided into two groups recurrent aphthous group and control. Recurrent aphthous group comprised of 70 patients with active lesion and 70 age and sex matched healthy controls were included in the control group. Recurrent aphthous stomatitis was diagnosed on the basis of history and clinical examination. Serum ferritin levels were measured by ELISA using Absorbance Microplate Reader, ELX 800, BioTek Instrument Inc. USA while serum iron and hemoglobin levels were measured by microlab 300.Based upon normal laboratory values, the iron levels were significantly low in RAS patients as compared to control.It was concluded that iron deficiency is related to recurrent aphthous stomatitis.
Keywords: iron; ferritin; hemoglobin